2022
DOI: 10.1111/mpp.13185
|View full text |Cite
|
Sign up to set email alerts
|

Xanthomonas hortorum – beyond gardens: Current taxonomy, genomics, and virulence repertoires

Abstract: Taxonomy Bacteria; Phylum Proteobacteria; Class Gammaproteobacteria; Order Lysobacterales (earlier synonym of Xanthomonadales); Family Lysobacteraceae (earlier synonym of Xanthomonadaceae); Genus Xanthomonas; Species X. hortorum; Pathovars: pv. carotae, pv. vitians, pv. hederae, pv. pelargonii, pv. taraxaci, pv. cynarae, and pv. gardneri. Host range Xanthomonas hortorum affects agricultural crops, and horticultural and wild plants. Tomato, carrot, artichoke, lettuce, pelargonium, ivy, and dandelion were origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 193 publications
(437 reference statements)
0
27
0
Order By: Relevance
“…The genus Xanthomonas includes plant-associated or plant-pathogenic bacterial species capable of infecting taxonomically diverse plant species [1, 2]. The pathogenic members of Xanthomonas cause devastating diseases in hundreds of annual crops, fruit trees and ornamental species [3].…”
Section: Full-textmentioning
confidence: 99%
“…The genus Xanthomonas includes plant-associated or plant-pathogenic bacterial species capable of infecting taxonomically diverse plant species [1, 2]. The pathogenic members of Xanthomonas cause devastating diseases in hundreds of annual crops, fruit trees and ornamental species [3].…”
Section: Full-textmentioning
confidence: 99%
“…vitians LM16734. From the inner to outer track are the mean read count over 1 kb in 1/10 th TSB and in lettuce, the gene state in the in vitro library, as described in reference 24 , the log 2 FC score in lettuce leaves compared to the inoculum, clustering of critical genes, pathways, functions and structural components in lettuce, gene names or locus tag identifiers, and chromosomal tracks.…”
Section: Resultsmentioning
confidence: 99%
“…vitians is considered a reemerging pathogen all around the world ( 18 , 20 23 ). Nowadays, very little is known about the biology of this pathogen during the infection process, and the molecular bases sustaining the host-pathogen interaction remain mostly unelucidated ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Virulence of most plant-pathogenic xanthomonads is attributed to the function of the T3SS and a set of transcription activator-like effectors (TALEs) and non-TALES or T3Es/Xops ( 7 , 50 ). Comparative genomics revealed that the crown gall-associated Xanthomonas strains might be adapted to a nonpathogenic lifestyle, which is reflected by the lack of pathogenicity gene clusters present in the pathogenic members of clade I ( Fig.…”
Section: Discussionmentioning
confidence: 99%